Seorang Wanita Usia 33 Tahun Dengan Diabetes Melitus Tipe II, Hipertensi Urgency, Anemia Mikrositik Hipokromik, Infeksi Saluran Kemih, dan Sindrom Nefrotik - Sri Meutia; Faizah Azzahara (Pusat riset dan Inovasi Nasional, 2025)
Type 2 diabetes mellitus (T2DM), hypertension, anemia, nephrotic syndrome, and urinary tract infection (UTI) are interrelated clinical conditions frequently encountered in patients with chronic kidney disease (CKD). This case report presents a 33-year-old woman who was admitted with complaints of generalized weakness, accompanied by headache, generalized edema, and pruritus. Laboratory findings revealed hyperglycemia (>300 mg/dL), elevated blood pressure (210/120 mmHg), increased urea and creatinine levels, 2+ proteinuria, and microcytic hypochromic anemia (hemoglobin ranging from 7.9 to 9.9 g/dL). Urinalysis showed leukocyturia, hyaline casts, and bacteriuria. The patient was diagnosed with uncontrolled T2DM, hypertensive urgency, microcytic hypochromic anemia, nephrotic syndrome, and UTI. Management included basal-bolus insulin regimen, combined antihypertensive therapy, packed red cell transfusions, and supportive treatments. Throughout the hospitalization, improvements were observed in hemoglobin levels and blood pressure, although subjective symptoms such as fatigue and headache remained fluctuating. This case highlights the importance of comprehensive and multidisciplinary management in patients with complex multisystem chronic conditions to prevent complications and improve clinical outcomes.